How did smokers respond to standardised cigarette packaging with new, larger health warnings in the United Kingdom during the transition period? A cross-sectional online survey. (2nd January 2020) - Moodie, Crawford; Brose, Leonie S.; Lee, Hyun S; Power, Emily; Bauld, Linda
Abstract: Introduction: In the United Kingdom, standardised packaging for cigarettes was phased in between May 2016 and May 2017. We assessed whether there was an association between using standardised packs and warning salience, thoughts about the risks of smoking, thoughts about quitting, and awareness and use of stop-smoking websites. Methods: We conducted a cross-sectional online survey with current smokers aged 16 and over ( N = 1865) recruited in two regions of England between February-April 2017, when both standardised and fully-branded packs were on the market. Participants were asked about use of standardised packs, warning salience (noticing, reading closely), and whether the packs they were using increased thoughts of the risks of smoking and quitting. They were also asked about awareness of stop-smoking websites, source of awareness (including warnings on packs), and whether they had visited a stop-smoking website. Results: Most participants reported currently using standardised packs (76.4%), 9.3% were not currently using them but had previously used them, and 14.3% had never used them. Compared with never users, current users were more likely to have noticed the warnings on packs often/very often (AOR (95%CI) = 2.76 (2.10, 3.63)), read them closely often/very often (AOR(95%CI) = 2.16 (1.51, 3.10)), thought somewhat/a lot about the health risks of smoking (AOR(95%CI) = 1.92 (1.38, 2.68)), and thought somewhat/a lot about quitting (AOR(95%CI) = 1.90 (1.30, 2.77)). They were also more likely to have noticed a stop-smoking website on packs. Conclusions: Consistent with the broad objectives of standardised packaging, we found that it was associated with increased warning salience and thoughts about risks and quitting.